Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/14713012221148780
|View full text |Cite
|
Sign up to set email alerts
|

Dementia knowledge among physiotherapists in Nigeria

Abstract: Background With the growing population of older adults in Nigeria comes a simultaneous rise in the incidence of dementia in the country. Adequate knowledge of dementia is needed to effectively administer interventions for persons living with dementia. Physiotherapy is one of the professions providing care for people with dementia. The aim of this study was to evaluate the knowledge of dementia among physiotherapists in Nigeria. Methods An online survey method was used to collect data from the sample population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Bridging the gaps and moving dementia and cognitive impairment out of the shadows in French-speaking Sub-Saharan Africa Brain health in general, and cognitive impairment (including dementia) in particular, is under-studied and still subject to misconceptions and taboos in FS-SSA. The dementia knowledge de cits in the general population but also among health professionals constitute a limiting factor for optimal care for the patients from receiving [187]. Therefore, it is crucial that far-reaching and widely publicized awareness campaigns are carried out in these countries to demystify dementia/cognitive problems, while empowering communities for better care and less stigma towards affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Bridging the gaps and moving dementia and cognitive impairment out of the shadows in French-speaking Sub-Saharan Africa Brain health in general, and cognitive impairment (including dementia) in particular, is under-studied and still subject to misconceptions and taboos in FS-SSA. The dementia knowledge de cits in the general population but also among health professionals constitute a limiting factor for optimal care for the patients from receiving [187]. Therefore, it is crucial that far-reaching and widely publicized awareness campaigns are carried out in these countries to demystify dementia/cognitive problems, while empowering communities for better care and less stigma towards affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the Australian version was found to have the lowest Cronbach’s alpha (0.7) [ 49 ]. The DKAT2 has also been translated into Brazilian Portuguese [ 50 ] and was also administered in the Nigerian population using the English translation [ 51 ], but no psychometric properties, other than item analysis, are available from their studies. To our knowledge, the DKAT2 has not been validated in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our research design, their study was an online survey, while the characteristics of the sample data were similar to ours, which may explain the similarity between the two studies in terms of item analysis. Item 1 was also the easiest answer for Nigerian physiotherapists, as mentioned by Onyekwuluje et al (2023) [ 51 ]. The Spanish version by Parra-Anguita et al (2018) [ 47 ] revealed six very easy items, which is the highest percentage in the already existing studies.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural beliefs and superstitions additionally fuel misconceptions about the origins and repercussions of dementia in the Nigerian context. The resultant stigma manifests in fear and isolation, extending to avoidance behaviors even among healthcare professionals [38, 39]. These observations underscore the imperative of an ongoing collaborative effort involving government agencies, healthcare professionals, community leaders, and advocacy groups to address and mitigate awareness gaps and stigma associated with dementia.…”
Section: Introductionmentioning
confidence: 99%